Effect of in situ synthesized and additives on the thermal performance of mullite thermal storage ceramics. Issue 20 (15th October 2022) - Ye, Fen; Cheng, Hao; Shi, Wei; Chang, Jun; Liu, Song
Abstract: High-performance thermal storage ceramics can enable utilization of solar thermal power generation plants. In this work, in situ synthesis was used to prepare mullite thermal storage ceramics. Calcined bauxite, talc, and kaolin were used as raw materials. The effects of additives (e.g., SiC, Si3 N4, TiC, and ZrB2 ) on the density, mechanical durability, phase components, microstructure, and thermal performance of the mullite ceramics were studied. The results showed that the thermal expansion coefficient, thermal conductivity, and heat storage density of the mullite ceramics were affected by their phase components. SiC and Si3 N4 did not decompose during the in situ syntheses, but TiC and ZrB2 decomposed. With the addition of 10  wt % SiC, the thermal conductivity improved to 2.72 W (m K) −1 (298 K). The heat storage density of this material was 688 kJ kg −1 (273–1073 K). Consequently, the in situ synthesized mullite thermal storage ceramic with added SiC could be a promising candidate material for a compound latent-sensible heat storage system.